APLIKASI PERHITUNGAN EFFORT PERANGKAT LUNAK DENGAN METODE PUTNAM’S MODEL - Frankie Frankie; Lely Hiryanto; Bobby Tumbelaka (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Computer technology has developed so much in this last few years. It has already been used by everyone in many aspects even in daily life. Computer technology itself is made by hardware and software. Those two parts stands together to form a technology that can be used by everyone. Hardware is kind of tool or device that is used to runs software. Software is a program that has many kinds depends on need. Software itself is built by codes that is written in various programming language. Software helps people in doing their works. Measuring value of a software is not an easy thing, especially to know the effort needed in writing source code. This program is made to calculate the effort estimation of a software. The method used to calculate the effort is Putnam’s Model which used productivity value of many source code as a model. Key wordsEffort Estimation, Software, Putnam’s Model